MARKETING STRATEGY BASED ON CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TO INCREASE CUSTOMER RETENTION - Saida Zainurossalamia ZA (Adisam Publisher, 2025)
This research aims to systematically examine various Customer Relationship Management (CRM) based marketing strategies that are effective in increasing customer retention. In an era of increasingly tight business competition, retaining old customers has proven to be more efficient than acquiring new customers. Therefore, CRM is a crucial strategic approach in creating and maintaining long-term relationships between companies and customers. This study uses a literature review method of various scientific articles, Scopus and Sinta indexed journals, as well as other relevant publications published in the last ten years. The study results show that CRM strategies which include service personalization, marketing automation, customer feedback management, data-based loyalty programs, and the use of analytics and digital technology have proven effective in increasing customer loyalty and retention. However, the success of implementing this strategy is influenced by a number of supporting factors such as technological readiness, customer-centric organizational culture, human resource competence, and the quality of customer data management. Thus, proper implementation of CRM not only increases customer retention but also provides a sustainable competitive advantage to the company.